PENGARUH VARIASI SUHU TERHADAP LAJU KOROSI PADA BAJA ST 37 DENGAN MENGGUNAKAN INHIBITOR KULIT JAGUNG - Ratih, Ratih; Rahmaniah, Rahmaniah; Agus, Jasdar (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2023)
Research has been carried out which aims to determine the efficiency of corn husk extract in inhibiting the corrosion rate of St37 steel by using the mass loss method, to determine the effect of immersion temperature variations in inhibiting the corrosion rate of ST37 steel and to determine the effect of variations in inhibitor concentration in inhibiting the corrosion rate of steel. ST37. the method used in this study is the method of mass loss (Mass Loss). As for the results of the research that has been done, corn husks can inhibit the corrosion rate which is used as an inhibitor on ST37 steel by using 3% HCl medium with temperature variations of 40oC, 50oC and 60oC. The results of the corrosion rate without inhibitors obtained 40oC of 32.98 mpy, 50oC of 62.09 mpy, 60oC of 71.51 mpy. And the results of the corrosion rate using a fixed inhibitor concentration of 400 ppm obtained 40oC of 32.81 mpy, 50oC of 36.59 mpy, 60oC of 38.76 mpy.